Aphasia rehabilitation in Australia: Current practices, challenges and future directions. (April 2014) - Rose, Miranda; Ferguson, Alison; Power, Emma; Togher, Leanne; Worrall, Linda
Abstract This study reports on current aphasia rehabilitation practices of speech-language pathologists in Australia. A 30-item web-based survey targeted approaches to aphasia rehabilitation, education, discharge, follow-up practices, counselling, interventions to improve communication access, community aphasia support services, and challenges to practice. One hundred and eighty-eight surveys were completed representing ˜ 33% of the potential target population, with 58.5% urban and 41.5% rural participants across all states and territories. Respondents reported embracing a wide variety of approaches to aphasia rehabilitation; however, significant challenges in providing aphasia management in acute and residential care were identified. Low levels of knowledge and confidence were reported for both culturally and linguistically diverse clients and discourse approaches. Group and intensive services were under-utilized and clinicians reported inflexible funding models as major barriers to implementation. Few clinicians work directly in the community to improve communicative access for people with aphasia. Despite the chronic nature of aphasia, follow-up practices are limited and client re-entry to services is restricted. Counselling is a high frequency practice in aphasia rehabilitation, but clinicians report being under-prepared for the role. Respondents repeatedly cited lack of resources (time, space, materials) as a major challenge to effective service provision. Collective advocacy is required to achieve system level changes.